Parental willingness to vaccinate adolescent daughters against human papilloma virus for cervical cancer prevention in Western Nigeria - Akinleye, Haleemat Wuraola (Pan Afr Med J, 2020)
INTRODUCTION: cervical cancer, which is vaccine preventable, is the commonest gynaecological cancer worldwide. This study aimed to assess parental willingness to vaccinate adolescent girls against human papillomavirus (HPV) for cervical cancer prevention. METHODS: this was a descriptive cross-sectional study among 301 parents of adolescent girls who reside in Surulere Local Government Area in Lagos, Nigeria. A pretested, semi-structured interviewer-administered questionnaire was used to collect data and analysis was done using Epi-info™ version 7. The chi-square (or Fisher’s exact) test and the t-test were used to test for associations between categorical and continuous variables respectively. The level of significance was set at 0.05. RESULTS: over half (53.5%) of the respondents had heard of cervical cancer. Of these, two thirds (62.1%) were aware that it could be prevented, 19.0% had good knowledge of cervical cancer prevention, only 4% had their daughters vaccinated though 79.2% were willing to vaccinate. The poor vaccine uptake was mostly due to lack of awareness of vaccination centres and the high cost of the vaccine. Willingness was significantly associated with level of education (p = 0.047) and knowledge of HPV vaccination (p < 0.001), however once aware, most parents were willing to get their daughters vaccinated. CONCLUSION: awareness about cervical cancer prevention was high though uptake was low. A high level of education and good knowledge of cervical cancer prevention were facilitators of willingness to vaccinate, though once aware parents were willing. Creating awareness and educating parents about cervical cancer prevention is essential in improving the uptake of the vaccine.